2010
DOI: 10.1109/lcomm.2010.09.100594
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Chase Decoding of Reed-Solomon Codes

Abstract: Abstract-In this letter, we propose a probabilistic approach to the generation of test patterns in the Chase Algorithm (CA) denoted as the Stochastic Chase Algorithm (SCA). We compare the performance of SCA with the regular CA for different ReedSolomon codes. Simulation results show that the probabilistic nature of the SCA helps in providing a more efficient test pattern generation. SCA avoids the use of least reliable bits selection and reduces the number of candidate codewords up to 60% for the same decoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…In its original form, Chase decoding incurs the complexity of performing hard decoding multiplied by a factor that is exponential in the number of unreliable bits. Improvements to this approach make use of the stochastic nature of errors to enhance performance [34], [35], [36], [37], [38], [4], but with improvement of the order of halving, on average, the number of operations. A thorough overview of Chase decoding for BCH and Reed-Solomon codes, and of the recent developments in incorporating soft information in decoding, is provided in [4].…”
Section: Related Workmentioning
confidence: 99%
“…In its original form, Chase decoding incurs the complexity of performing hard decoding multiplied by a factor that is exponential in the number of unreliable bits. Improvements to this approach make use of the stochastic nature of errors to enhance performance [34], [35], [36], [37], [38], [4], but with improvement of the order of halving, on average, the number of operations. A thorough overview of Chase decoding for BCH and Reed-Solomon codes, and of the recent developments in incorporating soft information in decoding, is provided in [4].…”
Section: Related Workmentioning
confidence: 99%
“…The soft input for the IEED decoder is the reliability of each bit, which can be represented in the probability domain as [11],…”
Section: Model Of the Communication System And Notations Used In The mentioning
confidence: 99%
“…The log likelihood ratio (LLR) for the bit i, j in the received sequence is given by [11] r i,j = L(x i,j |y i,j ) = log P(x i,j = 1|y i,j ) P(x i,j = −1|y i,j ) ,…”
Section: Model Of the Communication System And Notations Used In The mentioning
confidence: 99%
“…In [11], it was shown that this algorithm provides better performance with a reduced number of test vectors compared to the Chase algorithm. From a hardware implementation perspective, Step 2 can be implemented by using a single decoding unit and reusing it for each test vector.…”
Section: Stochastic Chase Decoding Algorithmmentioning
confidence: 99%
“…In terms of hardware complexity, the least reliable bits selection and the test vector construction take a non-negligible part of the decoder. In [11], a stochastic version of the Chase algorithm was proposed. It allows the number of test vectors to be reduced and the least reliable bits selection to be replaced by independent stochastic units.…”
Section: Introductionmentioning
confidence: 99%